Do desemprego a precarizacao: a experiencia dos catadores da Associacao Reciclando do Bairro Tancredo Neves, Fortaleza/CE, ante as transformacoes do mundo do trabalho - Falcão, Milena Bezerra de Sousa (2007)
Throughout history, work has experienced intense transformations that seem to become day by day faster and of difficult assimilation. During a great part of the industrial society until the middle of the 70?s. The unemployment was a great threat for workers, but recently, another phenomenon, the work precarization, has been revealed as a notable delineation of the labor world. This transformation is the start of the present work. Another relevant aspect for this study is the importance of thinking about the solid residues discarding process, the garbage. It is a problem that is also presented in the current context. The joint of these two processes is the result of the reflection undertaken here. This study aims to understand the experience of the recycled material collectors in relation to the labor precarization process, considering the impact of the work world transformations and its relation with unemployment and precarization. The research involved recycled material collectors, in its majority, that belong to the same Association that made part of a pilot-project promoted by the Government of the State of the Cear? in the 90?s. For data collection we used observation and half-structuralized interviews. The data had been analyzed based on the content analysis. The results had indicated relevant data concerning labor precarization, as some aspects had been evidenced, such as extensive hours of working, decreasing hygiene and security conditions, low incomes, work conditions instability, fragile social rights. All the interviewed ones had affirmed to perform this activity as a way to surpass the unemployment, however, they had indicated a desire to change to another labor activity. Although they belong or wish to belong to the Association, they had not demonstrated envolvement with the collective project and remain performing the activity in an individualizing way, reaffirming the ?neoliberal? speech of individuality. The social utility of recycled material collectors must be thought by the society, keeping in mind that labor precarization and environment degradation are aspects that coexist in the contemporary times.